2013
DOI: 10.1039/c3cp43399d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations into the nucleation of silica growth in basic solution part I – ab Initio studies of the formation of trimers and tetramers

Abstract: We have performed the first ab initio study that considers all possible oligomerization reactions available to silicic acid in basic solution (ignoring high-energy multiply charged species), up to and including tetramers. Energies have been computed at the MP2/6-31+G(d)//HF/6-31+G(d) level of theory, with a hybrid solvation model which includes explicit waters and CPCM continuum corrections to account for solvent effects. The explicit waters have been found to be extremely important in providing additional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(78 citation statements)
references
References 58 publications
9
69
0
Order By: Relevance
“…11 Recently, ab initio studies have been conducted to elucidate the mechanism for polymerization of silicic acid into all forms of tetrameric silica. 12,13 Th e models show good correlation with experimental data in terms of dependency of polymerization reaction rates on pH and temperature. Despite mainly providing new fundamental knowledge about silica polymerization, such studies can provide valuable information about silica chemistry and reaction kinetics which can potentially be benefi cial for controlling silica in biorefi neries.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…11 Recently, ab initio studies have been conducted to elucidate the mechanism for polymerization of silicic acid into all forms of tetrameric silica. 12,13 Th e models show good correlation with experimental data in terms of dependency of polymerization reaction rates on pH and temperature. Despite mainly providing new fundamental knowledge about silica polymerization, such studies can provide valuable information about silica chemistry and reaction kinetics which can potentially be benefi cial for controlling silica in biorefi neries.…”
Section: Introductionmentioning
confidence: 58%
“…Recently, ab initio studies have been conducted to elucidate the mechanism for polymerization of silicic acid into all forms of tetrameric silica . The models show good correlation with experimental data in terms of dependency of polymerization reaction rates on pH and temperature.…”
Section: Silica Chemistrymentioning
confidence: 85%
“…43,44 In addition, McIntosh benchmarked a series of electronic levels of theory, selecting finally a hybrid approach as a good compromise between accuracy and computational cost. He initially argued that 8 water molecules suffice to converge the theoretical activation barriers and pre-exponential factors with respect to the number of water molecules.…”
Section: Review Articlementioning
confidence: 99%
“…44 For instance, explicit water molecules do raise the barriers of the trimer cyclization reaction, but lower the relative stability of the silica three-ring. 44 For instance, explicit water molecules do raise the barriers of the trimer cyclization reaction, but lower the relative stability of the silica three-ring.…”
Section: Review Articlementioning
confidence: 99%
“…These small units, called pre-nucleation clusters 49 , have been thoroughly studied in the case of silica-rich solutions, both experimentally [11][12][13][14][15][16][17][18] and theoretically 19,21,[50][51][52] . It has been shown that their average concentration depends on several factors such as temperature, initial silica concentration, pH and the presence of additional cations.…”
Section: B Formation Of Oligomers In the Aqueous Solutionmentioning
confidence: 99%